االحتجاج باالستصحاب وأثره يف اختالف الفقهاءإعداد: عبد الوهاب أحمد خليل - Abdul Wahab Ahmad Khalil (Institut Agama Islam Negeri (IAIN) Kediri, 2017)
Islam is a complete and comprehensive religion. The comprehension of Islam does not lie in the completeness of the verses of the Qur’an and the words of Hadith, because in fact the verses of the Qur’an and the words of Hadith are limited, meanwhile the human problems continue to grow. So, the role of ijtihad as a means of reform of Islamic law is vital. One of the methods of ijtihad is Istishâb. This study describes the meaning of Istishâb, scholars’ opinion about the value of its strength as a source of law, as well as the influence of scholars’ opinion about the value of his resistance to differences of opinion in Islamic law. This study concludes that the majority of scholars of the Maliki, Shafii, and Hambali sect assert that Istishâb is a hujjah to defend (daf’i) and establish something (itsbat). The late ulamas of the Hanafi sect assert that Istishâb is a hujjah in defense of something, while the majority of the Hanafi scholars and some scholars of the Shafi’i sect state that Istishâb is not a hujjah at all. The difference of the ulama’s view of the use of Istishâb in ijtihad has led to differences in their views on Islamic law, as in the case of the law of the disappeared’s inheritance. In addition, the existence of Istishâb becomes a solution to find out contemporary Islamic law, Especially In the field of criminal law, personal status and civil law.